Rancangan Manajemen Proyek Komputer Pada PT Lovalattes Indonesia - Agung Wijoyo; Ahmad Fajri; Moh. Ridzki Alif Maulana; Nazila Iva Sugianisa; Rio Ardy Milala (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Role technology in solving all difficulties is demanded by the progress of the times, human desire for high work problems,and  information technology. Electronic commerce, sometimes known as "e-commerce," is the process of buying and selling of goods, services, and information via computer networks. Internet is one network that is used. Companies can more effectively build commercial partnerships with customers or partners by connecting their network computer to internet. E-commerce can increase the productivity and cost-effectiveness of a business, increasing its competitiveness